Learn Jawi using gaming approach on mobile devices / Norizan Mat Diah, Marina Ismail and Suzana Ahmad - Mat Diah, Norizan; Ismail, Marina; Ahmad, Suzana (Research Management Institute (RMI), 2012)
Students are exposed to various learning environments such as classrooms, schools and at home with their family. Traditional method used in school give the controls on overall learning procedures including the methods and materials to the assigned teachers. At the same time the teachers are required to design the teaching material on their own. Most application developed for mobile devices are not educational oriented but emphasis more on entertainment purposes. Although similar educational application is developed for personal computers, but very few are for mobile devices and none for learning Jawi. Research main objectives are, to design content for learning Jawi through mobile game for children aged 10 to 12 years old based on Jawi Syllabus in Malaysian primary schools and to develop a prototype of an interactive mobile game based on the design. Based on the evaluation that has been conducted on children about learning Jawi on mobile, children are delighted to use the application. Children are hooked on the application and repetitively trying to accomplish the task designed in the application. This shows that mobile application is a good alternative approach for teaching and learning of Jawi writing.